2022
DOI: 10.1177/11786302221111865
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Computer Vision Syndrome Among Academic Staff in the University of Gondar, Northwest Ethiopia: An Institution-Based Cross-Sectional Study

Abstract: Introduction: Computer vision syndrome (CVS) is the leading occupational hazard of the 21st century, which causes the critical public health issues in the present era. In developing countries, including Ethiopia, data on the proportion and the causes of CVS are scarce among academic staff for policy conclusions. Accordingly, this study was conducted to determine the prevalence and factors associated with CVS among academic staff at the University of Gondar. Methods: Institution-based cross-sectional study desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
2
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 56 publications
(136 reference statements)
1
25
2
5
Order By: Relevance
“…Similarly, previous studies reported that the prevalence of this eye problem was higher among students with eye diseases and who wore glasses [ 8 , 9 , 12 , 29 ]. However, this study disagrees with other studies [ 7 , 19 , 24 ]. Something that could explain this discrepancy is that the young university population does not yet have a worn crystalline lens, and therefore, there is an absence of DES; however, this aspect needs to be addressed exhaustively in other research because it is an occupational disease that is not considered a priority but that, with the passage of time, can cause irreversible consequences for vision.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Similarly, previous studies reported that the prevalence of this eye problem was higher among students with eye diseases and who wore glasses [ 8 , 9 , 12 , 29 ]. However, this study disagrees with other studies [ 7 , 19 , 24 ]. Something that could explain this discrepancy is that the young university population does not yet have a worn crystalline lens, and therefore, there is an absence of DES; however, this aspect needs to be addressed exhaustively in other research because it is an occupational disease that is not considered a priority but that, with the passage of time, can cause irreversible consequences for vision.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the prevalence of DES that was revealed by this study is lower than that reported in studies that considered the presence of DES with at least one symptom [ 7 , 22 ]. In turn, it is higher compared to studies that considered between six and nine symptoms [ 11 , 13 , 17 , 23 , 24 ]. Nevertheless, the high DES prevalence among Peruvian nursing students reported here is consistent with studies carried out among university students in other countries during the COVID-19 pandemic [ 9 , 17 ] and professionals who worked in front of a computer [ 16 , 22 ].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Moreover, its symptoms affect almost 70% of all computer users [8]. CVS causes reduced work e ciency and productivity, a higher rate of errors, poor job satisfaction, and a reduced quality of life for the computer worker [11,12]. CVS can reduce productivity by up to 40% [12].…”
Section: Introductionmentioning
confidence: 99%